Inter-Layer Prediction Scheme for Scalable 3-D Holoscopic Video Coding - Conti, C. (2013)
Holoscopic imaging has recently become a prospective glassless 3-D technology conquering the attention of researchers seeking more realistic depth-illusion approaches. However, backward compatibility with legacy displays is crucial to progressively introduce this technology into the consumer market and to efficiently deliver 3-D holoscopic content to end-users. Therefore, this letter proposes a new display scalable coding solution for 3-D holoscopic based on an inter-layer prediction scheme that exploits the redundancy between multiview and 3-D holoscopic content representations. Experimental results show that this inter-layer prediction scheme integrated into the High Efficiency Video Coding (HEVC) is advantageous, always outperforming the simulcast approach.